A "Smart Lock" for Preventing Hepatitis B Entry into Cells. Issue 7 (19th July 2018) - Balzarini, Madeline; Kodadek, Thomas
Abstract : In this issue of Cell Chemical Biology, Passioura et al. (2018) report another interesting application of the powerful random non-standard peptide integrated discovery (RaPID) screening method. They identify several high-affinity macrocyclic peptides for the sodium taurocholate co-transporting polypeptide (NTCP), the protein through which hepatitis B virus (HBV) enters the cell. Abstract : In this issue of Cell Chemical Biology, Passioura et al. (2018) report another interesting application of the powerful random non-standard peptide integrated discovery (RaPID) screening method. They identify several high-affinity macrocyclic peptides for the sodium taurocholate co-transporting polypeptide (NTCP), the protein through which hepatitis B virus (HBV) enters the cell.